Novi organizacijski model Hrvatske pošte i telekomunikacija - Slavko Jaram (Promet - Traffic&Transportation, 1970)
Postal and telecommunication infrastructure facilities make integral parts of the overall traffic and broadly-aspect economic system of any country. This paper deals with the new model of management structure of the Croatian Posts and Telecommunications (HPT), made upon the one-time abandoned pattern of organization as originally based upon the principles of self-management decentralization. Consequently, a new far more efficient and viewed socially far more rational organization system of posts and telecommunications has been required. The exposed organization model has been designed as a unique system with two sub-systems: Postal Authorities and Telecommunications Authorities linked with joint functions (services). On this basis, consequently, the organization of individual levels of postal and telecommunications network and individual geographic regions have been structured. Each organization i.e. management level has been structured according to the contents and scope of its assignments and the area of the region it covers. By way of interaction of organization (management) units, the organizational unity of the system has been achieved. This way the regular maintenance of the postal and telecommunications network is secured as well as the regular and standardized quality of domestic and international postal and telecommunications traffic.